Human genetics of infectious diseases: the example of bacterial/mycobacterial infections - Abel, Laurent (Henry Stewart Talks, 2009)
General strategy for investigating human genes in infectious diseases, A continuous spectrum from Mendelian to complex predisposition, Mendelian predisposition to invasive pneumococcal disease, Mendelian predisposition to mycobacterial infections including tuberculosis, Complex predisposition to tuberculosis and leprosy